2022
DOI: 10.3390/ijms24010212
|View full text |Cite
|
Sign up to set email alerts
|

Fraxetin Interacts Additively with Cisplatin and Mitoxantrone, Antagonistically with Docetaxel in Various Human Melanoma Cell Lines—An Isobolographic Analysis

Abstract: Malignant melanoma is a skin cancer characterized by rapid development, poor prognosis and high mortality. Due to the frequent drug resistance and/or early metastases in melanoma, new therapeutic methods are urgently needed. The study aimed at assessing the cytotoxic and antiproliferative effects of scoparone and fraxetin in vitro, when used alone and in combination with three cytostatics: cisplatin, mitoxantrone, and docetaxel in four human melanoma cell lines. Our experiments showed that scoparone in the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Thus, our experiments and isobolographic analysis showed that the combinations of esculetin and cisplatin are characterized by additive interactions. An additive interaction was also observed for the combination of cisplatin and osthole for two melanoma cell lines, FM55P and FM55M2 [5], and for the combination of cisplatin with fraxetin (7,8-dihydroxy-6-methoxycoumarin) for four malignant melanoma cell lines [6]. Our experiments showed that the combinations of esculetin with taxanes (paclitaxel and docetaxel) also showed additive interactions, although the combination of fraxetin with docetaxel showed an additive interaction with a tendency to antagonism [6], which may be due to the different chemical structure of fraxetin compared to esculetin.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Thus, our experiments and isobolographic analysis showed that the combinations of esculetin and cisplatin are characterized by additive interactions. An additive interaction was also observed for the combination of cisplatin and osthole for two melanoma cell lines, FM55P and FM55M2 [5], and for the combination of cisplatin with fraxetin (7,8-dihydroxy-6-methoxycoumarin) for four malignant melanoma cell lines [6]. Our experiments showed that the combinations of esculetin with taxanes (paclitaxel and docetaxel) also showed additive interactions, although the combination of fraxetin with docetaxel showed an additive interaction with a tendency to antagonism [6], which may be due to the different chemical structure of fraxetin compared to esculetin.…”
Section: Discussionmentioning
confidence: 83%
“…They can be used not only in the prevention of cancer but also in its treatment. Tested individually (for a better understanding of the mechanisms of anticancer activity) or in combination with other substances, they become an interesting target for the development of more beneficial forms of therapy [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Combination of these drugs with esculetin decreases cell viability, cell proliferation, and cytotoxicity, including arrest of the cell cycle in the G1 phase, induction of cytochrome c, p53, p21, and p27 expression, reduction of CDK2 and CDK4 expression and prevention the binding interaction between Nrf2 and KEAP-1 in the range of concentrations of 2-200 μM in human malignant melanoma cell lines (FM55P, A375, FM55M2, and SK-MEL28). 96 Morin, and esculetin supplementation effectively target tumor metabolism via β-cateinin/cmyc signaling and affect glycolysis and glutaminolysis to abrogate colon cancer in rats. 47 Regarding treating leukemia, the combined use A summary of the combined effect of esculetin with other phytochemical and chemotherapeutics agents is shortlisted in Table 4.…”
Section: Potential Synergy Of Esculetin With Other Agents In Cancer T...mentioning
confidence: 99%
“…Epirubicin, and vemurafenib showed antagonistic interactions with esculetin, while cisplatin, docetaxel, and paclitaxel showed additive interactions with esculetin. Combination of these drugs with esculetin decreases cell viability, cell proliferation, and cytotoxicity, including arrest of the cell cycle in the G1 phase, induction of cytochrome c, p53, p21, and p27 expression, reduction of CDK2 and CDK4 expression and prevention the binding interaction between Nrf2 and KEAP‐1 in the range of concentrations of 2–200 μM in human malignant melanoma cell lines (FM55P, A375, FM55M2, and SK‐MEL28) 96 . Morin, and esculetin supplementation effectively target tumor metabolism via β‐cateinin/c‐myc signaling and affect glycolysis and glutaminolysis to abrogate colon cancer in rats 47 .…”
Section: Potential Synergy Of Esculetin With Other Agents In Cancer T...mentioning
confidence: 99%
“…Drug combination therapy, using platinum-based antitumor drugs in combination with different target cytotoxic drugs, is an effective strategy to enhance the anticancer efficacy and overcome the drug resistance of platinum drugs in tandem with reduced toxicity. , For example, the combination chemotherapeutic regimen of cisplatin with tubulin inhibitors (e.g., paclitaxel and docetaxel) was used for the treatment of several major solid tumors as a frontline agent in the clinic; oxaliplatin in combination with folinic acid and 5-fluorouracil as a three-component chemotherapy protocol was used to treat colorectal cancer . However, this strategy of the concurrent use of two or more drugs remains a challenge because of unpredictable drug–drug interactions as each individual drug has its own pharmacokinetic profile as well as toxicity pattern.…”
Section: Introductionmentioning
confidence: 99%